2021
DOI: 10.15575/jra.v1i3.15089
|View full text |Cite
|
Sign up to set email alerts
|

Studi Perbandingan Fitur-Fitur Aplikasi Al-Quran Digital Karya Greentech Apps Foundation dan Aplikasi Al-Quran Muslim Media untuk Mengetahui Perbedaan Kedua Fitur aplikasi

Abstract: Digitalization of the Koran is a process of changing the vehicle from the beginning of the Koran being limited to written printed form to digital, for example, the Koran (tafsir and pe — word) by Greentech Apps Foundation and al-Quran interpretation and word by word by Muslim Media. Not many people know information about the background of the formation and differences related to the features of the two applications. The purpose of this research is to find out the background of the formation, features, advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The practicality of digital Quran applications is also a significant factor in the increasing interest of users (Andika et al, 2021). Users do not need to carry a large and heavy physical Quran everywhere (Arifin et al, 2020).…”
Section: The High Interest and Usage Of Digital Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The practicality of digital Quran applications is also a significant factor in the increasing interest of users (Andika et al, 2021). Users do not need to carry a large and heavy physical Quran everywhere (Arifin et al, 2020).…”
Section: The High Interest and Usage Of Digital Applicationsmentioning
confidence: 99%
“…The fifth can listen to audio or murottal (Andika et al, 2021), In this category, the writer found that LPTQ students utilize a digital Al-Qur'an application to listen to MP3 audio or recitations within the application. The application offers numerous features and a wide range of options with famous reciters.…”
Section: The Functions Of a Digital Quran Applicationmentioning
confidence: 99%
“…Al-Qur`an merupakn landasan hukum yang dijadikan sebagi pedoman hiidup umat muslim. Al-Qur`an berisikan firman-firman Allah SWT yang diturunkan kepada Nabi Muhammad SAW dengan perantara ruh alamin (malaikat jibril) untuk di baca, dipahami dan diamalkan, sebagai kitab suci umat islam (Yani et al, 2021).…”
Section: Hasil Dan Pembahasanunclassified